Evaluation of implant fit and frontal plane alignment after bi-compartmental knee arthroplasty using patient-specific instruments and implants - Arnholdt, Joerg (Arch Med Sci, 2018)
INTRODUCTION: The goals of successful bi-compartmental knee arthroplasty are to achieve correct fit and positioning of the implant, while appropriately correcting the mechanical alignment of the leg after surgery. As these requirements are not always reliably fulfilled using off-the-shelf implant systems, newer approaches for bi-compartmental resurfacing have been explored. MATERIAL AND METHODS: In this article we report the radiographic results of 30 patients with anteromedial osteoarthritis (OA) who were treated with a novel patient-specific fixed-bearing bi-compartmental knee resurfacing system using custom-made implants and instruments. Utilizing standardized pre- and postoperative radiographic analyses (based on anterior-posterior and lateral, anterior-posterior weight-bearing full-length radiographs, patella skyline views and preoperative computed tomography (CT) scanning) implant fit and positioning as well as correction of the mechanical axis (hip-knee-ankle angle, HKA) were determined. RESULTS: On average, HKA was corrected from 173.4 ±3.47° preoperatively to 179.4 ±2.85° postoperatively. The coronal femoro-tibial angle was corrected on average 5.61°. The preoperative tibial slope measured on lateral views was 6.38 ±2.4°, while the average slope in the CT-based planning protocol (iView) was 6.14 ±2.40°. Postoperative lateral tibial slope was determined to be 5.77 ±1.97°. The thickness of the posterior femoral cuts was measured intraoperatively and, in all cases, corresponded well to the targeted thickness of the cuts provided by the iView. The joint line was preserved in all cases and the average Insall-Salvati index was 1.078 ±0.11 pre- and 1.072 ±0.11 postoperatively. The fit of the implant components measured by over- or underhang was excellent throughout (< 1.01 mm). CONCLUSIONS: Custom-made bicompartmental knee arthroplasty can ensure optimized fitting and positioning of the implant with restoration of the leg axis. These implants could be considered as an alternative primary solution for knee surgeons treating bi-compartmental disease.